Ruminal metabolic development in conventionally or early weaned calves - K.L. Anderson; Tiruvoor G. Nagaraja; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1986)
Accelerating the weaning age of calves appeared to increase their ruminal metabolic activity. This was indicated by the lower ruminal pH and increased, total volatile fatty acid concentration of calves weaned at 4 wk of age compared with those weaned at 6 wk of age.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Ruminal microbes; Metabolic activity; Lactic acid; Volatile fatty acid